Multicomponent body composition of university club sport athletes - Dale R. Wagner; Edward M. Heath; Sara A. Harper; Elizabeth A. Cafferty; Masaru Teramoto; Alyssa Evans; Tate Burch; Jacob McBride; Steven Spencer; Michael N. Vakula (Journal of the International Society of Sports Nutrition)
Background The body composition of National Collegiate Athletic Association (NCAA) athletes is well documented but no such data exist for university club sports athletes. Additionally, the majority of norms for NCAA athletes were created from individual methods requiring assumptions.Objective This study used a four-component (4C) model to measure the body composition of university club sports athletes.Methods Data were collected on club athletes participating in baseball, climbing, cycling, figure skating, gymnastics, ice hockey, lacrosse, pickleball, powerlifting, racquetball, rodeo, rugby, soccer, swimming, ultimate, and volleyball. The 4C model consisted of body volume, total body water, and bone mineral content measured by air displacement plethysmography, bioimpedance spectroscopy, and dual-energy x-ray absorptiometry, respectively. Percentile ranks were created for body fat percentage (%BF) and fat-free mass index (FFMI). Mean differences across teams were quantified with Cohen’s d.Results In total, 225 athletes (137 men, 88 women) completed data collection. Athletes varied in competitive experience (1 to 22 y) and body mass index (16.9 to 36.4 kg·m−2). The density of the FFM was significantly greater than the assumed value of 1.100 g·cm−3 for both men (p = .043) and women (p = .011). The %BF ranged from 4.9% to 35.7% (14.3 ± 5.8% BF) for men and from 15.5% to 42.8% (25.2 ± 6.0% BF) for women. FFMI ranged from 15.6 kg·m−2 to 26.8 kg·m−2 (30.0 kg·m−2 outlier removed) for men and from 14.1 kg·m−2 to 22.6 kg·m−2 for women. Differences across sports in %BF and FFMI were considered large-sized effects (d ≥ 0.80) for both men and women. Weight-sensitive sports (e.g. cycling and climbing) had the lightest athletes and were among the leanest, whereas power athletes (e.g. powerlifting and rugby) were among the heaviest athletes and had the highest FFMI.Conclusions Differences in %BF and FFMI are evident across sports. Due to the small sample size, use caution when interpreting the data as reference values for club sports athletes.